Análise dos transtornos mentais na população infanto-juvenil atendida nos serviços de atenção psicossocial de Cuiabá, 2015 - Quintal, Aline Pifano Neto (2018)
The epidemiology of mental disorders of childhood and adolescence is of great value in understanding the origins and course of psychiatric disorders and contributing to the design of preventive and therapeutic interventions. Objective: To analize the mental disorders diagnosed in children and adolescents attended at psychosocial care services in Cuiabá, MT, 2015. Method: This is a cross-sectional study based on secondary data obtained from the medical records of the population served in 2015 at the Child and Adolescent Psychosocial Care Center (CAPSi) and the Medical Specialties Center (CEM) outpatient clinic. The dependent variables were age group (children and adolescents) and severity of the diagnosis (moderate/severe and mild). To verify associations with the independent variables, chi-square or Fisher's exact tests were performed with p<0.05. To verify the association of the variables in children in relation to the adolescent, prevalence ratios (PR) with a 95% confidence interval (95%CI) were performed. PR moderate/severe in relation to mild with 95% CI were also performed. Variables with p<0.20 and "missing">30% entered the final Poisson regression model. Results: The majority were adolescents (56.6%), male (70.8%), similar race/color distribution (54.5% black). The main diagnoses were: neurodevelopmental disorders (54.7%), depressive disorders (16.1%) and schizophrenia spectrum (9.1%). The types of neurodevelopmental disorders that showed association in children in relation to adolescents were: autism spectrum disorders (PR=1.44, 95%CI=1.18-1.76) and intellectual disability (PR=0.66, 95%CI=0.50-0.87). After multivariate analysis, remained associated with the children in relation to adolescents: neurodevelopmental disorders (RP=1.78, 95%CI=1.18- 2.70); severity of symptoms moderate/severe (PR=1.27, 95%CI=1.03-1.55); spectrum of schizophrenia (PR=0.20, 95%CI=0.05-0.89); other disorders (PR=0.30, 95%CI=0.09-0.99) and drug treatment (PR=0.77, 95%CI=0.54-0.83). After multivariate analysis, remained associated with severity of symptoms moderate/severe: place of attendance CAPSi (PR=4.91, 95%CI=2.09-11.60); (PR=1.73, 95%CI=1.22-2.45), risk of serious harm to self (PR=1.93, 95%CI=1.42-2.63); drug treatment (PR=2.23, 95%CI=1.58-3.14); mental disorder of the father (PR=0.60, 95%CI=0.41-0.87). Conclusion: These findings suggest the need for health care professionals´ training in early diagnosis, treatment and rehabilitation of these pathologies to increase the mental health problem solving capacity of the primary care team. Regarding severity, the CAPSi significantly responded to a higher proportion of moderate/severe cases, just as the CEM predominantly attended milder cases, taking into account the population for which they were intended.